Expatriate cross-cultural adjustment in multinational corporations / Amir Hamzah Mohd Zainal - Mohd Zainal, Amir Hamzah (Faculty of Business and Management, 2020)
Expatriate and expatriation have become a norm in today’s business environment where business operations transcend beyond the national border. Globalization had provided the opportunity for entrepreneurs and corporations to expand their market and fulfilled the potential for growth in other geographic areas. The study aimed to discuss the elements that influenced expatriate cross-cultural adjustment during their international assignment in Malaysia. A theoretical framework consisted of three variables; personality traits, cultural intelligence and spousal/family support was developed. The fundamental question addressed in this study was to determine the factors that influenced expatriate cross-cultural adjustment. The research objectives were to examine the relationship between the personality traits, cultural intelligence and spousal/family support towards expatriate cross-cultural adjustment. Expatriates that are employed in multinational corporations (MNCs) and had resided in Malaysia for more than six months were chosen as respondents for the study. Data were collected through questionnaires distributed to 103 expatriates using non-probability sampling. Data analysis were conducted using frequency, descriptive, reliability, correlational and regression analysis. Based on the analysis, the findings indicated that personality traits and cultural intelligence had a significant and positive relationship toward expatriate cross-cultural adjustment.